A AQUISIÇÃO FONOLÓGICA DO INGLÊS COMO L2 À LUZ DA OT: OS VERBOS CONTENDO A MARCA «-ED» - Alves, Ubiratã (Organon, 2004)
This paper focuses on the acquisition, by Brazilian Portuguese speakers, of both the syllabicstructure and the sonority of the coda segments of the English verbs containing the morpheme “-ed”.The analysis which was developed under the framework of Optimality Theory was able to show theevolution of the learners’ constraint ranking from the initial state H0 to the hierarchy which led tonative-like production. The analysis has also shown that, regarding the acquisition of the syllabicstructure, the production of native-like forms implied not only the demotion of constraints, but also theabandonment of an input originated from the written form, and the subsequent acquisition of a newunderlying representation which was able to lead to the production of the target structures. In thisregard, the analysis has revealed that, as for L2 acquisition, variable output forms do not need to besolely originated from the constraint ranking, given the fact that such outputs may also come from theexistence of more than one input representation maintained by the same learner